Unified Fault-tolerant Control Strategy with Torque Ripple Compensation for Five-phase Permanent Magnet Synchronous Motor Based on Normal Decoupling - Guodong Sun; Guijie Yang; Yanyi Wang; Jianyong Su (Energies, 2019)
In this paper, the decoupling matrix in a five-phase permanent magnet synchronous motor (FPMSM) is rebuilt and changed, according to different open-phase conditions, which complicate the switch and control algorithm. This paper proposes a unified fault-tolerant control strategy with decoupling transformation matrix, effectively suppressing the torque ripple for several open-phase faults. The current algorithms for different open-phase faults are demonstrated; torque ripple, especially, is analyzed with third harmonic magnetomotive force (MMF). The unified current control law is expressed with two adjustable coefficients, which are regulated for torque ripple compensation. As the current control equation remains unchanged, the fault-tolerant can smoothly switch from normal to fault condition, only with different coefficients. The proposed method with torque compensation (TC) can realize effective suppression of torque ripple. The decoupling relationship between open-phase control laws and fault-tolerant current is verified by simulation. The torque ripple of fault-tolerant and effect of torque compensation (TC) under all fault-tolerant conditions are simulated by finite element simulation. The stability of switching and correctness of torque compensation are verified by experiments.